A systematic review of cardiovascular emergency department visits, hospital admissions and mortality associated with ambient black carbon. (October 2017) - Luben, Thomas J.; Nichols, Jennifer L.; Dutton, Steven J.; Kirrane, Ellen; Owens, Elizabeth O.; Datko-Williams, Laura; Madden, Meagan; Sacks, Jason D.
Abstract: Background: Black carbon (BC) is a ubiquitous component of particulate matter (PM) emitted from combustion-related sources and is associated with a number of health outcomes. Objectives: We conducted a systematic review to evaluate the potential for cardiovascular morbidity and mortality following exposure to ambient BC, or the related component elemental carbon (EC), in the context of what is already known about the associations between exposure to fine particulate matter (PM2.5 ) and cardiovascular health outcomes. Data sources: We conducted a stepwise systematic literature search of the PubMed database and employed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for reporting our results. Study eligibility criteria: Studies meeting inclusion criteria (i.e., include a quantitative measurement of BC or EC used to characterize exposure and an effect estimate of the association of the exposure metric with ED visits, hospital admissions, or mortality due to cardiovascular disease) were evaluated for risk of bias in study design and results. Study appraisal and synthesis methods: Risk of bias evaluations assess some aspects of internal validity of study findings based on study design, conduct, and reporting and identify potential issues related to confounding or other biases. Results: The results of our systematic review demonstrate similar results for BC or EC and PM2.5 ; that is, a generally modest, positive association of each pollutant measurement with cardiovascular emergency department visits, hospital admissions, and mortality. There is no clear evidence that health risks are greater for either BC or EC when compared to one another, or when either is compared to PM2.5 . Limitations: We were unable to adequately evaluate the role of copollutant confounding or differential spatial heterogeneity for BC or EC compared to PM2.5 . Conclusions and Implications of Key Findings: Overall, the evidence at present indicates that BC or EC is consistently associated with cardiovascular morbidity and mortality but is not sufficient to conclude that BC or EC is independently associated with these effects rather than being an indicator for PM2.5 mass. Systematic review registration number: Not available. Highlights: Regional differences in PM2.5 -related health effects are often observed and may be explained by differences in PM2.5 components observed in different geographical regions We examine whether or not there is clear evidence for an independent effect of BC, separate from that attributed to PM2.5, on cardiovascular morbidity and mortality. Our results demonstrate generally similar risk for BC or EC and PM2.5 ; that is, generally modest, positive associations of each of these pollutant measurements with cardiovascular outcomes. The possibility that the similarities in results for BC or EC and PM2.5 could be due to greater exposure measurement error due to the greater spatial heterogeneity of BC and EC, especially in the presence of on-road sources, cannot be ruled out. Our systematic review indicates that BC or EC is consistently associated with cardiovascular morbidity and mortality, but is not sufficient to conclude that BC or EC is not just an indicator for PM mass